THE EFFECT OF CASH FLOW, LEVERAGE, GROWTH OPPORTUNITIES AND COMPANY SIZE ON WORKING CAPITAL MANAGEMENT - Fajar Rakasiwi Syamsuddin (Jurnal Ekonomi, 2023)
This study aims to determine the relationship between Cash Flow, Leverage, Growth Opportunities and Company Size on Working Capital Management as measured by the Cash Conversion Cycle. This study uses a quantitative approach with multiple regression analysis tools. Sample Using food and beverage sub-sector manufacturing companies listed on the Indonesian stock exchange. The dependent variable is working capital management proxied by the cash conversion cycle. The longer the cycle, the more funds are invested in working capital, indicating the need for additional capital. While the independent variables consist of cash flow, leverage, growth opportunities and company size. This study found that growth opportunities and debt policies had a positive and significant effect on the company's working capital management. Aggressive selling and use of debt will result in a longer cash conversion cycle for the company. This study also found that company size and cash flow had no effect on the company's working capital management.